Endothelial nitric oxide synthase Glu298Asp gene polymorphism influences body composition and biochemical parameters but not the nitric oxide response to eccentric resistance exercise in elderly obese women. (5th June 2015) - Teixeira, Tatiane Gomes; Tibana, Ramires Alsamir; Nascimento, Dahan da Cunha; de Sousa, Nuno Manuel Frade; de Souza, Vinicius Carolino; Vieira, Denis César Leite; Nóbrega, Otávio de Toledo; de Almeida, Jeeser Alves; Navalta, James; Prestes, Jonato
Summary: Both endothelial nitric oxide synthase (eNOS) gene polymorphism and nitric oxide (NO) are involved in important cardiovascular, muscular and inflammatory physiological mechanisms during ageing and response to exercise. The aim of this study was to investigate the NO kinetic response following an acute eccentric resistance exercise (ERE) session and the possible effect of the Glu298Asp eNOS gene polymorphism in elderly obese women. Eighty‐seven women (age 69·4 ± 6·1 years, body weight 74·9 ± 12·7 kg, height 151·9 ± 6·0 cm and BMI 32·5 ± 5·7 kg m −2 ) completed seven sets of ten eccentric repetitions at 110% of the ten repetitions maximum (10RM). NO concentrations remained elevated up to 48 h following the acute ERE session as compared with baseline, for GG and GT/TT groups ( P <0·05), with no differences between genotypes. The GG genotype group had higher body weight, prevalence of obesity (BMI classification – 81% versus 56%), BMI and higher relative muscle strength, while they had significantly lower triglycerides, VLDL and urea concentrations as compared with TT/TG group. In conclusion, NO remains elevated for up to 48 h after an acute ERE session, without genotype interaction. The TT/TG genotype had a negative impact on triglycerides, VLDL and urea concentrations. Thus, T carriers should increase their attention to cardiovascular risk factor and metabolic disorders.